Mathematics and Computation in Music Second International Conference, MCM 2009, John Clough Memorial Conference New Haven, CT, USA, June 19-22, 2009. Proceedings - Chew, Elaine; Childs, Adrian; Chuan, Ching-Hua.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the Second International Conference on Mathematics and Computation in Music, MCM 2009, held in New Haven, CT, USA, in June 2009. The 26 revised full papers presented were carefully reviewed and selected from 38 submissions. The MCM conference is the flagship conference of the Society for Mathematics and Computation in Music. The papers deal with topics within applied mathematics, computational models, mathematical modelling and various further aspects of the theory of music. This year$1 (Bs conference is dedicated to the honor of John Clough whose research modeled the virtues of collaborative work across the disciplines.s
Hamiltonian Cycles in the Topological Dual of the Tonnetz -- The Continuous Hexachordal Theorem -- Speech Rhythms and Metric Frames -- Temporal Patterns in Polyphony -- Maximally Smooth Diatonic Trichord Cycles -- Towards a Symbolic Approach to Sound Analysis -- Plain and Twisted Adjoints of Well-Formed Words -- Regions and Standard Modes -- Compatibility of the Different Tuning Systems in an Orchestra -- Formal Diatonic Intervallic Notation -- Determining Feature Relevance in Subject Responses to Musical Stimuli -- Sequential Association Rules in Atonal Music -- Badness of Serial Fit Revisited -- Estimating the Tonalness of Transpositional Type Pitch-Class Sets Using Learned Tonal Key Spaces -- Musical Experiences with Block Designs -- A Generalisation of Diatonicism and the Discrete Fourier Transform as a Mean for Classifying and Characterising Musical Scales -- The Geometry of Melodic, Harmonic, and Metrical Hierarchy -- A Multi-tiered Approach for Analyzing Expressive Timing in Music Performance -- HMM Analysis of Musical Structure: Identification of Latent Variables Through Topology-Sensitive Model Selection -- A Declarative Language for Dynamic Multimedia Interaction Systems -- Generalized Voice Exchange -- Representing and Estimating Musical Expression in Melody -- Evaluating Tonal Distances between Pitch-Class Sets and Predicting Their Tonal Centres by Computational Models -- Three Conceptions of Musical Distance -- Pairwise Well-Formed Scales and a Bestiary of Animals on the Hexagonal Lattice -- Generalized Tonnetz and Well-Formed GTS: A Scale Theory Inspired by the Neo-Riemannians.
Keywords: Computer science; Music; Computer science -- Mathematics; Application software; Algebra; Mathematical models; Computer Science; Computer Appl. in Arts and Humanities; Mathematical Modeling and Industrial Mathematics; Mathematics of Computing; Music; Algebra; Electronic books